2019
DOI: 10.1101/610618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered structural hub connectivity and its clinical relevance in glioma

Abstract: Background and Purpose: Structural network analysis of diffusion imaging is increasingly used to study neurological disease, its pathophysiology and symptoms. We therefore evaluate structural hub connectivity in glioma patients and its association with molecular subtype and clinical status.Materials and Methods: Using retrospective diffusion imaging, structural connectivity was investigated in 65 newly diagnosed glioma patients (36 males; mean age 52 ± 14 years) and 60 healthy controls (23 males; mean age 50 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…As we mentioned above, hub neuronal regions play a central role in the brain small-world network and can be clustered into a rich club. Glioma patients, however, have more hub-related connections in the contralateral hemisphere ( Yu et al, 2016 ; Douw et al, 2019 ; Yuan T. et al, 2020 ), while a slight difference in the ipsilateral hemisphere was found. These contralesional connections suggested the decompensation of structure and function and the particular redistribution of connectivity ( Crossley et al, 2014 ; Stam, 2014 ).…”
Section: Structural Connectome and The Alternations In Gliomasmentioning
confidence: 87%
“…As we mentioned above, hub neuronal regions play a central role in the brain small-world network and can be clustered into a rich club. Glioma patients, however, have more hub-related connections in the contralateral hemisphere ( Yu et al, 2016 ; Douw et al, 2019 ; Yuan T. et al, 2020 ), while a slight difference in the ipsilateral hemisphere was found. These contralesional connections suggested the decompensation of structure and function and the particular redistribution of connectivity ( Crossley et al, 2014 ; Stam, 2014 ).…”
Section: Structural Connectome and The Alternations In Gliomasmentioning
confidence: 87%
“…Extratumoural preand post-operative Neurite Density within the fronto-parietal and DMN had a protective factor in memory recovery that may be mediated by the prominent role of these networks in this cognitive domain. From the connectomic perspective, cognitive performance of brain tumour patients has been associated with hub-related structural connectivity within the DMN and fronto-parietal Network in hemispheres contralateral to the tumour 44 . By using connectomic metrics derived from both DTI and fMRI, Liu et al (2016) achieved a 75% accuracy when predicting survival of high-grade glioma patients 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Extratumoural pre- and post-operative Neurite Density within the Fronto-parietal and DMN had a protective factor in memory recovery that may be mediated by the prominent role of these network in this cognitive domain. From the connectomic perspective, cognitive performance of brain tumour patients has been associated with hub-related structural connectivity within the DMN and Frontoparietal Network in hemispheres contralateral to the tumour[Douw et al, 2019]. By using connectomic metrics derived from both DTI and fMRI, Liu et al (2016) achieved a 75% accuracy when predicting survival of high-grade glioma patients[Liu et al, 2016].…”
Section: Discussionmentioning
confidence: 99%